Investigation of Japan Disaster Medical Assistance Team response guidelines assuming catastrophic damage from a Nankai Trough earthquake - Anan, Hideaki; Kondo, Hisayoshi; Akasaka, Osamu; Oshiro, Kenichi; Nakamura, Mitsunobu; Kiyozumi, Tetsuro; Yamada, Norihiko; Homma, Masato; Morino, Kazuma; Nakayama, Shinichi; Otomo, Yasuhiro; Koido, Yuichi (Acute medicine & surgery, 2017)
Aim Transporting critically ill patients outside of disaster‐affected areas for treatment is an important activity of Japan Disaster Medical Assistance Teams (DMATs). We investigated whether this activity is possible after possible catastrophic damage from a Nankai Trough earthquake. Methods Japan was divided into three areas based on the level of predicted damage (definitely, possibly, and non‐affected areas). A survey of DMATs and the locations of emergency base hospitals and intensive care units (ICUs) in each area was carried out, and the ability to support disaster areas was investigated. Next, a survey of wide‐area medical transport by Self‐Defense Force aircraft and the medical transport abilities of helicopter ambulances was carried out. The numbers of ICU beds in each area were compared, and the capacity to accept patients was investigated. Finally, subjects for further study were examined. Results The number of DMATs that could be sent from non‐affected areas was insufficient. The number of patients that can be transported by Self‐Defense Force aircraft and helicopter ambulance during the first 3 days was determined to be 1,443. The number of patients that can be accepted by ICUs in non‐affected areas was insufficient. A system needs to be developed to provide medical treatment for critically ill patients within disaster areas during the acute phase. This will require DMAT operational reforms and the creation of logistics systems such as the supply of resources for earthquake‐reinforced hospitals. Conclusion In addition to patient transport, systems to provide medical care inside disaster‐affected areas are needed. We investigated the specific medical response capabilities and considered Japan Disaster Medical Assistance Team activity guidelines that should be changed assuming a Nankai Trough earthquake. The investigations indicate an overwhelming shortage in the number of responding Disaster Medical Assistance Teams, aircraft transport capacity, and the number of intensive care unit beds that can accept critically ill patients estimated to need transport out of the affected areas.